Anatomical Trajectory of the Corrugator Supercilii Muscle in Koreans: Implications for Aesthetic and Clinical Practices - Park, Hyun Jin; Paulsen, Friedrich; Kim, Hongtae; Hur, Mi Sun (Aesthetic Surgery Journal, 2025)
Background: Understanding the attachment patterns of the corrugator supercilii (CS) muscle is vital for treatments designed to improve facial symmetry and functionality. Objectives: The aim of this research was to elucidate the anatomical trajectory and intricate relationships of the CS within the upper face and midface, specifically focusing on its connections with the frontalis (FT) and orbicularis oculi (OOc) muscles. Methods: The CS was examined in 41 specimens of embalmed adult Korean cadavers with microdissection, histological analyses, and micro-computed tomography, performing an in-depth exploration of its anatomical positioning and the intricate interactions with adjacent muscles. Results: Some lower fibers of the CS extended to the upper orbital part of the OOc in 59.5% of cases, while the CS interdigitated or blended exclusively with the FT in 40.5% of cases. The fibers of the CS demonstrated diverse extensions toward the upper face and midface, exhibiting varied trajectories and lengths. Additionally, lower fibers of the CS extended to significant anatomical landmarks such as the OOc, malaris muscle, and the superficial musculoaponeurotic system (SMAS). Conclusions: In this study, we demonstrate that precise understanding of the CS and its relationship with the FT and OOc is crucial for optimizing invasive or noninvasive treatment like botulinum toxin injection, SMAS lifting, and browplasty surgery. The extension of lower fibers of the CS to significant anatomical landmarks indicates complex interactions with adjacent facial structures, highlighting the necessity of detailed anatomical knowledge for clinical applications.
CRIS-Team Scopus Importer:2025-04-01